A 3D dislocated re-entrant structure with compression-twist coupling effect - Chen, Xuan; He, Tengwu; Hu, Yandong; Feng, Miaolin (Smart materials and structures, 2023)
Compression-twist metamaterials are artificially designed materials which can realize transformation from axial compressing to twist loading. In this study, a new dislocation design of the 2D re-entrant hexagonal structure is proposed with the compression-shear coupling effect. Through orthogonal assembling, its 3D dislocation re-entrant structure is successfully obtained that exhibits compression-twist coupling effect. A theoretical model is built to clarify the deformation mechanisms of the novel structures, and relevant analyses indicate that the compression-twist coupling effects can be tuned by tailoring structure’s geometric parameters with a wide range of adjustable twist angles. Besides, the experiments and numerical simulations are also performed to verify our developed theoretical model, and finally more feasible structure designs are extended with compression-twist coupling effect based on the re-entrant structure. The novel 3D material structure with excellent compression-twist coupling effects provides new ideas for the design of compression-twist metamaterials.